The Discourse Perspective of Translation In Representing The Concept of ThÄâ€™at: Case Study of The Moral Ethic Book BidÄyatul HidÄyah - Anis, Muhammad Yunus (KARSA Journal of Social and Islamic Culture, 2017)
Translation is a rendering of form and meaning, but in the other hand, translation also can be defined as the rendering of message (amanah) from the source/start text into target text. This research elaborate the Arabic â€“ Javanese translation text. Arabic is the source language (L1) and Javanese is the target language (L2). The material object selected was the book of BidÄyatul-HidÄyah (Islamic Moral Ethic) written by Imam Al-Ghazali. This research investigate the personal image of Imam Al-Ghazali using the discourse perspective of translation. There are two basics problems in this research, (1) the translation of units language in the book of BidÄyatul HidÄyah in representing the concept of loyalty (thÄâ€™at) using the discourse perspective of translation, and (2) the concept of loyalty based on Imam Al-Ghazali in the book of BidÄyatul HidÄyah. The method had been divided into three basic steps: collecting the data using the observation method, analysis data related with the distributional method, and reporting the data. The result had been concluded that Imam al Ghazaliâ€™method to delivering the concept of loyalty (thÄâ€™at) message was the balancing between fiqh and sufism. Copyright (c) 2017 by KARSA. All right reservedÂ DOI: 10.19105/karsa.v25i1.1180Â